2016
DOI: 10.1038/labinvest.2015.152
|View full text |Cite
|
Sign up to set email alerts
|

Versican: a novel modulator of hepatic fibrosis

Abstract: Little is known about the deposition and turnover of proteoglycans in liver fibrosis, despite their abundance in the extracellular matrix. Versican plays diverse roles in modulating cell behavior in other fibroproliferative diseases, but remains poorly described in the liver. Hepatic fibrosis was induced by carbon tetrachloride treatment of C57BL/6 mice over 4 weeks followed by recovery over a 28-day period. Primary mouse hepatic stellate cells (HSCs) were activated in culture and versican was transiently knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 86 publications
(94 reference statements)
1
48
0
Order By: Relevance
“…Versican is an extracellular matrix protein belonging to a family of hyaluronan-binding proteoglycans. It is a major component of the fibroproliferative matrix in hepatic fibrosis and lung fibrosis (4,21). Consistent with our findings, Einecke et al evaluated the gene expression in 105 transplanted renal biopsies and found that versican was one of the most significantly upregulated genes and predicted renal graft loss in kidney transplantation (22).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Versican is an extracellular matrix protein belonging to a family of hyaluronan-binding proteoglycans. It is a major component of the fibroproliferative matrix in hepatic fibrosis and lung fibrosis (4,21). Consistent with our findings, Einecke et al evaluated the gene expression in 105 transplanted renal biopsies and found that versican was one of the most significantly upregulated genes and predicted renal graft loss in kidney transplantation (22).…”
Section: Discussionsupporting
confidence: 89%
“…Versican is a large extracellular matrix proteoglycan that is present in a variety of human tissues. Bukong et al reported that versican expression increased during liver fibrosis (4). Rienstra et al showed that versican expression was dominant during renal fibrosis in an experimental renal transplantation rat model (5).…”
Section: Introductionmentioning
confidence: 99%
“…Of these 48 genes, 35 encode extracellular proteins ( Figure 4B, highlighted in gray). Our attention was drawn to one of these, VCAN, which encodes an ECM protein recently implicated in the activation of HSCs (37) and that has also been linked to inflammation and cancer metastasis (38). VCAN mRNA expression strongly correlated with ELF score (r 2 value of 0.41) ( Figure 2) and was inducible by the profibrotic cytokine TGF-β in an EHF-dependent manner in the LX-2 HSC line ( Figure 3E).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is tempting to speculate that selective expression of the V0 and V1 isoforms in advanced fibrosis may have some role in HCC progression. Recently, VCAN was suggested to have a role in hepatic fibrosis, with in vitro studies showing that it promotes HSC activation (37). However, its role in driving inflammation and liver fibrosis during CLD is unknown.…”
Section: List Of 11 Degs (With 25-fold Difference In Expression Bementioning
confidence: 99%
“…Relative comparison of target gene expressions made use of the comparative ΔΔCt method with no treatment control serving as baseline reference for comparisons. The 18s RNA was used gene normalisation control similar to our previous reports (Ganz et al, 2015, Bukong et al, 2016). The following primer pairs were used.…”
Section: Methodsmentioning
confidence: 99%